2019
DOI: 10.14302/issn.2372-6601.jhor-19-2986
|View full text |Cite
|
Sign up to set email alerts
|

Genes in Tumor Formation

Abstract: With the definition of four gene classes, all differences between tumor cells and normal cells can be explained. Proliferative mutations induce a shortcut, forcing the cell to divide. They allow replication without control, induce somatic pairing defects of chromosomes and genome instability. Intact Tumor Supressors or mutant Switch Functions can inhibit this process. Oncogene mutations optimize the growth of the cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…A genetic and molecular study identified the central potential targets for therapeutic intervention in tumor cells: switch genes [1,2]. In tumor cells, the switch genes are overexpressed.…”
Section: Introductionmentioning
confidence: 99%
“…A genetic and molecular study identified the central potential targets for therapeutic intervention in tumor cells: switch genes [1,2]. In tumor cells, the switch genes are overexpressed.…”
Section: Introductionmentioning
confidence: 99%